Pengaruh Kompetensi Prajurit dan Kesiapan Materiel Tempur Batalyon Bekpal 2 Marinir terhadap Tugas Korps Marinir - Amirudin, Amirudin; Triutomo, Gunawan; Irfan, Muhammad (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The problem that researchers found in the field is that current material readiness needs to be optimized. Because the materials used greatly influence the main task of Yonbekpal 2 Marines, namely that carrying out logistical assistance must be supported by material readiness that is in accordance with the capabilities of the material. The objectives of this research are a. To test and analyze the influence of the competency of Marine Bekpal Battalion 2 soldiers on the duties of the Marine Corps, b. Testing and analyzing the influence of the combat material readiness of the 2nd Marine Bekpal Battalion on the tasks of the Marine Corps, c. To test and analyze the influence of soldier competency and combat material readiness of the 2nd Marine Bekpal Battalion simultaneously on the tasks of the Marine Corps. The method used in this research uses quantitative research methods. In this research, to determine the sample, the researcher used a probability sampling technique, namely simple random sampling. Data processing in this study used the SPSS 27 program. The study revealed that soldier competency in the 2nd Bekpal Marine Battalion contributed 32.9% (R²) to the effectiveness of Marine Corps operations, indicating a meaningful impact of individual skills and capabilities on mission performance. Combat material readiness accounted for a greater influence, with an R² of 55.5%, highlighting the critical role of equipment and logistical preparedness. When combined, both variables explained 61% of the variance in operational outcomes, suggesting a strong synergistic effect. SPSS analysis confirmed that both factors exert a positive and significant influence individually and jointly on Marine Corps task performance. These findings emphasize the strategic importance of enhancing both human resource development and material readiness to improve operational effectiveness and ensure mission success in complex military environments.